Nutritional impairment in ICU survivor: What should you do as healthcare provider? - Jamaludin, Thandar Soe Sumaiyah (2017)
Optimal nutritional requirements and nutrient intake composition for ICU survivors remain a partially unresolved issue. The clinical outcome of critically ill patients is improves by targeting nutritional support to the actual protein and energy needs. ICU survivors might be facing the risk for underfeeding and overfeeding which may be increased by factors interfering on nutrient need estimation, such as rapidly changing body weight due to fluid balance variations, nutrient losses and hidden calorie sources from their treatment.